TEOLOGI KONTEKSTUAL NOKEN SEBAGAI IDENTITAS BUDAYA MASYARAKAT TOLIKARA: KAJIAN ETNOGRAFI-TEOLOGIS DI JEMAAT GIDI CALVARI KOYA KARANG JAYAPURA - Godfried San Ferre; Hendrik Belwawin; Mika Gobai; Gusten Mallo (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The flow of globalization and digital technology penetration has gradually displaced local cultural symbols that form the foundation of indigenous community identity, including noken as a cultural heritage of the Tolikara people in Jayapura. This study aims to analyze the contextual theological meaning of noken as the cultural identity of the Tolikara community in the GIDI Calvari Koya Karang Jayapura Congregation. A qualitative method with an ethnographic-theological design was employed through participatory observation and in-depth interviews with church leaders, traditional leaders, and cross-generational congregation members. The results show that noken, known locally as Yumunggok, holds ontological depth as a